Improving electromagnetic noise removal from seismic data using innovative EM receivers: a novel hybrid approach - Mohammad Reza Gerivani; Mohamad Ali Riahi; Iraj Abdollahi-Fard (Discover Applied Sciences)
Abstract Considering the large extent of conventional seismic projects for hydrocarbon exploration, the electromagnetic (EM) noise from power grids is an inevitable challenge. Common methods for addressing this noise in seismic data follow a frequency-based elimination approach known to neglect the dynamic nature of the EM noise and negatively affect a part of the target signal along with the EM noise. In this work, a novel approach to EM noise attenuation was presented to resolve both drawbacks by introducing the new concept of “pure noise.” A special EM receiver was designed to record the EM noise, presumably apart from seismic signal or other noise, simultaneously with the seismic data recording. The recorded data was then phase- and amplitude-corrected through a couple of processing steps, and the result was subtracted from the raw data to achieve denoised seismic data. The proposed method was applied to a case study, where a 2D seismic line crossed two power lines operating at 230 and 132 kV. Results showed that the EM receivers recording at larger amplitudes were associated with smaller errors, which indicates the importance of the proper location of the EM receiver. The error of denoising on the test data was below 3%.